Local Revenue Collection and Service Delivery in Local Government: A Case Study of Tororo Municipal Council - Gloria Chemutai (Uganda Christian University, 2025)
This study investigated the effect of local revenue collection on service delivery in local government, focusing on Tororo Municipal Council in Uganda. The research specifically examined how three key components of revenue management—revenue mobilization, revenue assessment, and revenue enforcement affect the quality and sustainability of public services such as infrastructure, healthcare, education, and sanitation. Employing a cross-sectional research design, the study integrated both quantitative and qualitative methods to collect data from municipal employees and local government officials, achieving an overall response rate of 88.2%. Statistical analyses revealed that all three revenue management components have statistically significant positive effects on service delivery. Revenue mobilization showed a strong influence (β = 0.568, p < 0.001), explaining 30.8% of the variation in service delivery outcomes. Efficient revenue mobilization mechanisms enhance the council’s financial capacity, thereby improving the provision of essential services. Revenue assessment also positively impacted service delivery (β = 0.463, p < 0.001), accounting for 41.5% of the variation. Accurate, transparent, and regularly updated assessment practices ensure fair tax distribution, boosting revenue bases necessary for sustainable service financing. Revenue enforcement exhibited the strongest effect (β = 0.771, p < 0.001), explaining 62.3% of the variation. Strict enforcement policies such as audits, penalties, and compliance monitoring are critical for maximizing revenue collection and consequently improving public service quality. The study highlights challenges such as political interference, limited technological adoption, and informal sector predominance, which affect revenue collection effectiveness in the municipal context. Recommendations include adopting innovative tax collection methods, modernizing revenue assessment systems, and strengthening enforcement frameworks through digital platforms and transparency initiatives. Finally, the study calls for further research into the role of digital technology integration and socio-political factors influencing revenue collection and service delivery in Ugandan local governments. The findings contribute valuable empirical evidence to inform policy reforms aimed at enhancing local government financing and public service delivery.